Factors associated with severe human Rift Valley fever in Sangailu, Garissa County, Kenya. - A Desirée LaBeaud; Sarah Pfeil; Samuel Muiruri; Saidi Dahir; Laura J Sutherland; Zachary Traylor; Ginny Gildengorin; Eric M Muchiri; John Morrill; C J Peters; Amy G Hise; James W Kazura; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Mosquito-borne Rift Valley fever virus (RVFV) causes acute, often severe, disease in livestock and humans. To determine the exposure factors and range of symptoms associated with human RVF, we performed a population-based cross-sectional survey in six villages across a 40 km transect in northeastern Kenya. METHODOLOGY/PRINCIPAL FINDINGS:A systematic survey of the total populations of six Northeastern Kenyan villages was performed. Among 1082 residents tested via anti-RVFV IgG ELISA, seroprevalence was 15% (CI95%, 13-17%). Prevalence did not vary significantly among villages. Subject age was a significant factor, with 31% (154/498) of adults seropositive vs. only 2% of children ≤15 years (12/583). Seroprevalence was higher among men (18%) than women (13%). Factors associated with seropositivity included a history of animal exposure, non-focal fever symptoms, symptoms related to meningoencephalitis, and eye symptoms. Using cluster analysis in RVFV positive participants, a more severe symptom phenotype was empirically defined as having somatic symptoms of acute fever plus eye symptoms, and possibly one or more meningoencephalitic or hemorrhagic symptoms. Associated with this more severe disease phenotype were older age, village, recent illness, and loss of a family member during the last outbreak. In multivariate analysis, sheltering livestock (aOR = 3.5 CI95% 0.93-13.61, P = 0.065), disposing of livestock abortus (aOR = 4.11, CI95% 0.63-26.79, P = 0.14), and village location (P = 0.009) were independently associated with the severe disease phenotype. CONCLUSIONS/SIGNIFICANCE:Our results demonstrate that a significant proportion of the population in northeastern Kenya has been infected with RVFV. Village and certain animal husbandry activities were associated with more severe disease. Older age, male gender, herder occupation, killing and butchering livestock, and poor visual acuity were useful markers for increased RVFV infection. Formal vision testing may therefore prove to be a helpful, low-technology tool for RVF screening during epidemics in high-risk rural settings.